Analysis of The Implementation toward Employee Social Security at BPJS Employment - Novi Indraswari; Robiatul Arofa; Anggita Cahyaning Pratiwi; Badrut Tamam (Sharia Faculty, Kiai Haji Achmad Siddiq State Islamic University of Jember, 2024)
The Implementation of Social Security has been regulated in Law Number 24 of 2011 concerning the Employment Social Security Organizing Agency. BPJS Employment is the institution responsible for administering worker social security programs in Indonesia. BPJS Employment aims to provide social protection to workers and their families and promote the welfare of workers in this country. Analysis of the implementation of worker social security at BPJS Employment in the context of Law no. 24 of 2011 involves research into the policies, procedures and mechanisms used by BPJS Employment to provide social security to workers. The purpose of this analysis is to evaluate the extent to which BPJS Employment has implemented the provisions contained in the Employment Law and to identify potential problems or challenges in its implementation. Analysis of the implementation of worker social security at BPJS Employment in the context of Law no. 24 of 2011 provides a deeper understanding of the effectiveness and challenges faced in the worker social security system in Indonesia. The research method used in this paper is normative legal research. With the help of social security, these workers can minimize the poverty of working class families who are experiencing an economic crisis, as well as termination of employment.